The Science of Territorial Domination in General Haldimand’s Defence of Quebec, 1778-1783 - Gibson, Sarah (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2011)
In General Haldimand’s little-studied administration of Quebec during the American Revolutionary War, military strategy depended upon gathering information about the natural environment. Haldimand preserved Quebec for the British not by force, but by applying continental modes of territorial domination. Rather than secure the St. Lawrence Valley in an intimidating show of military force, Haldimand sought to secure the vitality of the fur trade along the Great Lakes corridor. This endeavor required Haldimand to look for the natural laws that created unity out of the social and geographic territory he had to defend, and to protect the most vital links: the economic currents and the transportation system. Thus, the Royal Engineers took precedence over other military officers as they collected a large body of information about the natural environment of the Great Lakes region. They drew maps, sounded bodies of water, and made meteorological observations, turning pleasant bays into safe harbors. The knowledge gathered replaced Mississaugan perspectives of the land, revised French information and set the agenda for Loyalist settlement in the region. This paper however, focuses upon Haldimand’s role in applying continental attitudes towards the landscape that helped solidify the link between natural history and imperialism of late-18th century Britain.